Pengaruh Money Ethics, Religiusitas, Tax Morale, dan Keadilan Pajak Terhadap Persepsi Wajib Pajak Mengenai Tax Evasion - Vivian Seputro, Johanna; Ratih, Suklimah (Jurnal Etnik: Ekonomi-Teknik, 2022)
Tax is a taxpayer's contribution to the state that is owed by an individual or entity that is coercive under the law. This tax plays a very important role in Indonesia's state finances, namely the annual State Revenue and Expenditure Budget (APBN). However, this tax revenue in Indonesia has not been fulfilled optimally. Taxpayers, both individuals and entities, generally tend to pay the lowest possible tax. Various ways are carried out by each taxpayer in order to minimize their tax obligations, one of which is the act of tax evasion. This resaerch aims to determine the effect of money ethics, religiosity, tax morality, and tax justice on taxpayers' perceptions of tax evasion. This research using primary data. sample selection using purposive sampling method and sample calculation using the Slovin formula. So that the research sample was found as many as 100 respondents. The results of this study indicate that the variables of money ethics and tax morale have a negative and significant effect on taxpayers' perceptions of tax evasion. While the variables of religiosity and tax justice have no significant effect on taxpayers' perceptions of tax evasion